2015
DOI: 10.9738/intsurg-d-14-00140.1
|View full text |Cite
|
Sign up to set email alerts
|

Suture Granuloma With False-Positive Findings on FDG-PET/CT Resected via Laparoscopic Surgery

Abstract: A 61-year-old woman who had undergone total hysterectomy 16 years previously exhibited a pelvic tumor on computed tomography (CT). F-18 fluorodeoxyglucose (FDG) combined positron emission tomography (PET)/CT imaging revealed a solitary small focus of increased FDG activity in the pelvis. A gastrointestinal stromal tumor originating in the small intestine or another type of tumor originating in the mesentery (desmoid, schwannoma, or foreign body granuloma) was suspected; therefore, laparoscopic resection was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Takeshita N et al, reported a case of pelvic suture granuloma in a 61-year-old female with a prior history of total hysterectomy for uterine myoma 16 years back and caesarean delivery 35 years back. 4 In this case, suture granuloma developed two years after the surgery. Authors opine that the inflammatory reaction is initiated in the early post-operative phase in all cases, but patients may become symptomatic after a variable time period.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Takeshita N et al, reported a case of pelvic suture granuloma in a 61-year-old female with a prior history of total hysterectomy for uterine myoma 16 years back and caesarean delivery 35 years back. 4 In this case, suture granuloma developed two years after the surgery. Authors opine that the inflammatory reaction is initiated in the early post-operative phase in all cases, but patients may become symptomatic after a variable time period.…”
Section: Discussionmentioning
confidence: 74%
“…Radiologically, suture granulomas can be mistaken as either primary malignancy or tumour recurrence in a surgically treated case of cancer. 1,[4][5][6][7][8] Rettenbacher et al, stated that suture granulomas would characteristically appear as hypoechoic lesion with hyperechoic single or double lines on USG. 9 But, most of the cases lack specific USG findings, like in this case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Including the present case, there have been 7 reports of 9 cases of suture granuloma with false-positive postoperative PET/CT findings [4] , [5] , [6] , [7] , [8] , [9] , [10] ( Table 1 ). As can be seen in Table 1 , the interval between surgery and suture granuloma occurrence varied significantly, and suture granuloma can be found several decades after surgery.…”
Section: Discussionmentioning
confidence: 91%
“…In our results, the mean maxSUV of foreign body granuloma was 4.41 (range, 2.2–7.2). A number of case reports have been published on this entity in various carcinomas [ 23 24 25 ]. However, only 1 or 2 cases were reported in each study and no large numbers of cases were identified, as in this study.…”
Section: Discussionmentioning
confidence: 99%